2010
DOI: 10.1074/jbc.m109.096172
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of Wall Teichoic Acid in Staphylococcus aureus by TarM

Abstract: Wall teichoic acid (WTA) glycopolymers are major constituents of cell envelopes in Staphylococcus aureus and related Gram-positive bacteria with important roles in cell wall maintenance, susceptibility to antimicrobial molecules, biofilm formation, and host interaction. Most S. aureus strains express polyribitol phosphate WTA substituted with D-alanine and N-acetylglucosamine (GlcNAc). WTA sugar modifications are highly variable and have been implicated in bacteriophage susceptibility and immunogenicity, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
149
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(158 citation statements)
references
References 61 publications
6
149
0
Order By: Relevance
“…These glycosyltransferases catalyze the addition either α- or β-linked GlcNAc, respectively, to the repeating phospho-ribitol unit. 29,34 Using these strains, we tested the ability of the panel of four antibodies to bind S. aureus that displayed WTA containing either α- or β-linked GlcNAc. Flow cytometry analysis showed that three antibodies, 4462, 4497 and 6078, bound the S. aureus USA300 ΔtarM , but not the S. aureus USA300 ΔtarS strain (Figure 2A-C).…”
Section: Resultsmentioning
confidence: 99%
“…These glycosyltransferases catalyze the addition either α- or β-linked GlcNAc, respectively, to the repeating phospho-ribitol unit. 29,34 Using these strains, we tested the ability of the panel of four antibodies to bind S. aureus that displayed WTA containing either α- or β-linked GlcNAc. Flow cytometry analysis showed that three antibodies, 4462, 4497 and 6078, bound the S. aureus USA300 ΔtarM , but not the S. aureus USA300 ΔtarS strain (Figure 2A-C).…”
Section: Resultsmentioning
confidence: 99%
“…Previous efforts in characterizing wall teichoic acid glycosyltransferases have employed partially purified enzymes and uncharacterized membrane acceptors to follow enzyme activity (18,19). We purified recombinant B. subtilis 168 TagE to homogeneity and developed an HPLC-based assay to examine the wall teichoic acid glycosyltransferase activity of the enzyme with clean synthetic substrates in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of this gene led to wall teichoic acid that completely lacked N-acetylglucosamine. The wall teichoic acid glycosyltransferase activity of TarM was subsequently confirmed by demonstration that crude extracts containing recombinant enzyme catalyzed the transfer of N-acetylglucosamine onto an uncharacterized membrane acceptor in vitro (18). Glaser and Burger (19) conducted the first and only in vitro study of poly(glycerol phosphate) polymer glycosylation in B. subtilis nearly 50 years ago.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular pathways of WTA glycosylation in S. aureus were recently elucidated (24,25). Two WTA glycosyltransferases, TarM and TarS, are responsible for modifying WTA with ␣-GlcNAc and ␤-GlcNAc, respectively.…”
mentioning
confidence: 99%